STRATEGI PENGELOLAAN MODAL KERJA DALAM MENJAGA TINGKAT LIKUIDITAS DAN PROFITABILITAS PADA BMT- AL HIDAYAH KABUPATEN LOMBOK TIMUR - Ainul Arofah; Zaenudinmansyur; Zulpawati (Jurnal Istiqro, 2024)
This research aimed to determine the working capital management  in maintaining liquidity and profitability levels and how the impact of the policy which has been implemented. This research was descriptive 0qualitative research using primary and secondary data, with data collection techniques namely observation, interviews and documentation of the financial reports from 2019 to 2021. The analysis used was data reduction, data presentation, drawing conclusions, and financial report analysis used the calculation of liquidity and profitability ratios.The results of the research showed that the working capital management policy used by BMT AI-Hidayah in maintaining the level of liquidity, namely establishing partnerships with sharia banks and non-banks, setting cash budgets, and allocating the funds to branch offices, while the policy used by BMT in maintaining its profitability level was distribution in the funding form. The impact of the policy implemented by BMT in terms of liquidity, namely having sufficient funds in its operations to pay the obligations. It can be seen in the ratio calculation from 2019 to 2021. NWC, current ratio, cash ratio  are in a fairly good category. the impact on the profitability side was that BMT has increased revenue and this can be seen in the ROE calcultion which is in the very good category,  while the ROI calcultion is in the fairly good category.